Hands on history : a resource for teaching mathematics - 4 0 16; Shell-Gellasch, Amy.; 5 Mathematical Association of America (Washington, DC : Mathematical Association of America, 2007)
Collects articles from researchers and educators who use models of a historical nature to enhance the mathematical reasoning, mechanical and spatial reasoning and manipulation, and evaluation skills of their students.
Includes bibliographical references.
Science Books & Films (A.A.A.S.)
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching (Secondary);Study and teaching (Higher);History.;Study and teaching.;History. -- Mathematics;Mathematics;Mathematics;Mathematical instruments.;Mathematics;Mathematics;Mathematical instruments; 20; 2